A new antifungal and antiprotozoal bibenzyl derivative from Gavilea lutea - Cretton, Sylvian; Oyarzun, Alejandra; Righi, Davide; Sahib, Lamia; Kaiser, Marcel; Christen, Philippe; Fajardo Morales, Victor Manuel (My University, 2018)
A new bibenzyl derivative (4), together with two glycosylated flavonoids (1 and 2), batatasin III (3) and the phenanthrene isohircinol (5) were isolated from the aerial parts of Gavilea lutea. Their structures were elucidated on the basis of spectroscopic studies including 1D and 2D NMR, UV, IR and HRESIMS. All isolated compounds were evaluated for their antifungal activity towards Candida albicans. The new compound 4 showed inhibitory activity with a MIQ of 50 mu g. In addition, compound 4 exhibited a selective activity (IC50 = 2.3 mu g/mL) against Leishmania donovani. [GRAPHICS] .
Keywords: gavilea lutea; bibenzyls; gavilein; antifungal activity; antiprotozoal activity